As transferências intergovernamentais e o reflexo na qualidade de vida da população nos municípios brasileiros - Silva, Evaldo José da (2020)
This study aimed to identify an existing relationship between intergovernmental transfers and the quality of life of the population in Brazilian municipalities. Such concern is justified in: (1) there are researches, not conclusive, which point to the sense of application of resources collected from attempts at execution and try a higher efficiency compared to the application of resources used by other means, like the intergovernamental grants, this is a reflection of events such as the flypaper effect and the theory of the determinants of public spending, without intergovernmental revenues; (2) the model of fiscal federalism adopted in Brazil, which approaches or makes public decisions about the demand for services by society, is with the aim of improving the quality of life of the population, which has among its characteristics or fact the cause of concentration of a volume of obligations in local locations exceeding the capacity for taxation, causing a vertical gap, that is, it is mandatorily corrected with the use of the transfer instrument. Compared to the theory that deals with the determinants of public spending and the literature on the flypaper effect, the work that had as the object of study the number of 4,158 Brazilian municipalities, from all geographic regions, which are given the necessary data to carry out the research. It was used in an economic regression model, with fixed effects estimates and panel data, using the IFDM-dependent variable, which served as a proxy for quality of life and as an explanatory variable, it was used in terms of the fund's participation level. municipalities (FPM) make up the current revenue of municipalities, representing as unconditional transfers. For control, the following variables were used: GDP per capita and social expenditure per capita of the municipalities. As the main finding of the research it was found that unconditional interferences, statistically significant way, quality of life of the population, therefore, an expected relationship of the highest percentage of intergovernmental transfers, the composition of the municipalities' revenues, results in a reduction in the quality of population life was statistically proven. This result points to the possibility that the Brazilian case converges with the theoretical-conceptual explanations that try to explain the aspects related to the relationship: the origin of the resource in public places and quality of life of the population, or that the implications of these theories explained in the reality of Brazil.